ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MASYARAKAT MENGAJUKAN PEMBIAYAAN DI BANK PEMBIAYAAN RAKYAT SYARIAH BOTANI DRAMAGA (Studi Kasus Kecamatan Ciampea Kabupaten Bogor) - Bunga Hidayatunnisa; Tubagus Rifqy Thantawi; Ermi Suryani (SAHID BANKING JOURNAL, 2022)
Basically, people who start a business tend not to have initial capital to start their business.because the economic conditions of the people in Ciampea District, Bogor are still low, withthe existence of Islamic People's Financing Banks (BPRS) to help people start their businesses anddevelop what they want. they dream of owning a business by applying for sharia financing to aBPRS, therefore BPRS must be able to attract public interest to apply for sharia financing. Based onreligiosity, good service quality, low public knowledge of the financial institution itselfadministrative costs, attractive promotions, and can adjust economic capabilitiespublic. This study aims to analyze the factors of religiosity, quality of service, publicknowledge, administrative costs, promotion and economic capacity to influence the public interestin applying for financing at BPRS Botani. This type of research is quantitative research andMethods of data collection using primary data obtained through questionnaires. Sampling amounted to 75 respondents, the technique of determining the sample using simple random samplingtechnique. The method used to test the hypothesis is multiple linear regression, t test, and f testcoefficient of determination (adjusted R square). The results of this study indicate that economic ability affects people's interest in applying for financing at BPRS Botani. Meanwhile, religiosity, service quality, public knowledge, administration costs, and promotions do not affect public interest in applying for financing at BPRS Botani.